Efektivitas Program Pendidikan dan Pelatihan di Sekretariat Jendral Dewan Perwakilan Daerah Republik Indonesia - Annissa Safitri Salsabilla (Perspektif Administrasi Publik dan hukum, 2025)
This study discusses Human Resources Education and Training at the Secretariat General of the Regional Representative Council of the Republic of Indonesia (DPD RI). The main issue faced by the Secretariat General of the DPD RI is that there are still employees who do not fully understand their respective fields. Therefore, a training program has been implemented to help employees enhance their knowledge and skills required for their duties. The purpose of this research is to analyze the effectiveness of education and training programs for human resources within the Secretariat General of the DPD RI. This research uses a descriptive qualitative method, with data collected through interviews, observations, and documentation. The results of the study show that employee understanding of one of the online-based training programs is still not optimal, indicating a need for improvements in content delivery or training methods. Nevertheless, the training targets are considered appropriate as they are directed at employees who require capacity enhancement. In terms of scheduling, the training program is considered to lack flexibility, which may interfere with the employees' daily work routines. Despite several challenges, the overall achievement of training objectives has had a positive impact on employee productivity. Real changes can be seen in the increased understanding and ability of employees to apply the knowledge gained to their tasks and responsibilities in each respective division. Thus, the education and training program is deemed to have made a significant contribution to the development of human resource competencies within the Secretariat General of the DPD RI.